Generating Cycles of Products and Prices - Moore, Henry Ludwell (Quarterly Journal of Economics, 1921)
The major features of economic cycles are traceable to three primary laws: (1) the law of the generating cycle of raw materials, which is due to a non-economic cause; (2) the law of demand for raw materials, in consequence of which the generating cycle of products originates a derived cycle of prices for raw materials; and (3) the law of competitive price, according to which the prices of finished goods in an open market tend to correspond with the cost of production. Correlation of crop yields and crop prices, 218. — Generating cycles of products. 224. — The derived cycle of prices, 226. — Cycles in the products of mines, 228. — Cycles in raw materials, 231. — Concluding observations, 233.